How Much Do Multicultural Residents of Greater Vancouver Know About the Internet? - Boshier, Roger; Kow, Janet Kushner; Huang, Yan (Alberta Journal of Educational Research, 2006)
Vancouver high school honors and university award lists are crowded with Asian names. But do these abilities in face-to-face settings extend to the Internet, which is the centerpiece of distributed learning? The purpose of this study was to measure the extent to which Internet knowledge varied as a function of age, sex, and language spoken at home. An Internet Quiz was administered to 3,537 residents in Greater Vancouver. Those who spoke English at home knew more about the Internet than those who spoke Chinese or other languages. The difference in English, Chinese, and other language scores possibly stemmed from relationships between Internet use and Internet knowledge, the pragmatism of Chinese in Greater Vancouver, the exigencies of immigration, and English-language dominance of the Internet.